Analysis of Factors Influencing Property Products in Ubud, Bali - Rudi Pranata Tjoa (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study aims to analyze the factors influencing the decision-making process for product development in Ubud, Bali. The research employs a quantitative approach. The population for this study consists of 900 customers and property developers involved in the property market in Ubud, Bali. To determine the required sample size, Slovin's formula was applied with a 5% margin of error, resulting in 286 respondents. Primary data was collected through questionnaires distributed to the respondents. The data analysis method used in this study is the Component or Variance-Based Structural Equation Model. The findings reveal that Customer Needs, Preferences, and Demands, Government Policies, Infrastructure Connectivity, and Socio-Cultural Conditions have a positive and significant impact on New Product Development decisions. Furthermore, it was identified that Customer Needs, Preferences, and Demands are the dominant factors influencing New Product Development decisions